VD_FINDINFO Arrêt / 2011 / 1247 vom 27. Oktober 2011 - VD Tribunal cantonal (2011)
CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION, OPPOSITIONPROCÉDURE, CHOIXEN GÉNÉRAL, CURATEUR | 379 CC, 380 CC, 381 CC, 388 al. 1 CC, 388 al. 2 CC, 388 al. 3 CC, 388 CC, 392 ch. 1 CC, 393 ch. 2 CC, 475 CPC, 489 CPC